Experimental demonstration of accurate Bragg peak localization with ionoacoustic tandem phase detection (iTPD). (16th December 2021) - Wieser, H P; Huang, Y; Schauer, J; Lascaud, J; Würl, M; Lehrack, S; Radonic, D; Vidal, M; Hérault, J; Chmyrov, A; Ntziachristos, V; Assmann, W; et al.
Abstract: Accurate knowledge of the exact stopping location of ions inside the patient would allow full exploitation of their ballistic properties for patient treatment. The localized energy deposition of a pulsed particle beam induces a rapid temperature increase of the irradiated volume and leads to the emission of ionoacoustic (IA) waves. Detecting the time-of-flight ( ToF ) of the IA wave allows inferring information on the Bragg peak location and can henceforth be used for in-vivo range verification. A challenge for IA is the poor signal-to-noise ratio at clinically relevant doses and viable machines. We present a frequency-based measurement technique, labeled as ionoacoustic tandem phase detection (iTPD) utilizing lock-in amplifiers. The phase shift of the IA signal to a reference signal is measured to derive the ToF . Experimental IA measurements with a 3.5 MHz lead zirconate titanate (PZT) transducer and lock-in amplifiers were performed in water using 22 MeV proton bursts. A digital iTPD was performed in-silico at clinical dose levels on experimental data obtained from a clinical facility and secondly, on simulations emulating a heterogeneous geometry. For the experimental setup using 22 MeV protons, a localization accuracy and precision obtained through iTPD deviates from a time-based reference analysis by less than 15 μ m. Several methodological aspects were investigated experimentally in systematic manner. Lastly, iTPD was evaluated in-silico for clinical beam energies indicating that iTPD is in reach of sub-mm accuracy for fractionated doses < 5 Gy. iTPD can be used to accurately measure the ToF of IA signals online via its phase shift in frequency domain. An application of iTPD to the clinical scenario using a single pulsed beam is feasible but requires further development to reach <1 Gy detection capabilities.